Transient model and its application to investigate the injection mode and periodical operation of transpiration cooling with liquid coolant phase change. (25th November 2020) - He, Fei; Dong, Wenjie; Wang, Jianhua; Zhou, Jianxing; Tang, Longsheng
Highlights: A transient model of transpiration cooling with phase change is developed. Dynamic phase change and fluid–structure coupling heat transfer are studied. Stability and reliability of coolant injection control modes are compared. Effects of fluctuated operation conditions on cooling performance are studied. Abstract: To study the stability and reliability of transpiration cooling with phase change in complicated and changeable thermal environment, this paper suggests a transient mathematical model and numerically investigates the dynamic evolution of phase change and transient behavior of fluid–structure coupling heat transfer under three typical time-varying thermal environments. First, the feasibility and reliability of two coolant injection methods are analyzed and compared. The results indicates that the coolant injection based on pressure control is stable only when the heat flux imposed on transpiration cooling structure is relatively low and phase change occurs at hot side, while the coolant injection based on mass flow rate control is absolutely stable no matter how the external thermal environment changes. Then, the effects of fluctuated operation condition on the cooling performance of system and the transport characteristic of coolant are further studied. Although without affecting the stability of the transpiration cooling system in the long term, the fluctuation of coolant injection and external heat flux will result in the fluctuation of structure temperature and coolant driving force, and thereby cause significant deterioration of cooling performance, which will increase the ablation risk and coolant driving cost of transpiration cooling system.